Developing an instrument with simulations to measure 3D to 2D fit correction skills in fashion design - Aditi Galada; Fatma Baytar (Fashion and Textiles)
Abstract In fashion design education, students are taught how to prepare 2D patterns to create 3D garments through flat pattern making and draping courses. However, there is a lack of focus on garment fitting, and students are expected to have a natural intuition regarding fit corrections. As a result, most students graduate without gaining the crucial skill of reading misfit signs in 3D and acting on correcting 2D patterns accordingly. For this reason, in the current study, we developed a novel skill test instrument based on the Extended Skill Cycle Model using 3D simulations to quantify students' fit correction skills. We evaluated the instrument’s reliability and validity for its suitability in teaching and research applications. Fit correction questions with virtual garment simulations were designed, and participants were provided with three potential pattern modification options, out of which one option corrected garment fit. The reliability of the questionnaire was determined using Cronbach’s alpha, and validity was analyzed by comparing pre- and post-training scores, comparing scores of participants with different levels of experience, and calculating the item difficulty and discrimination index. There was a positive correlation between the pre- and posttraining test scores, confirming that the instrument could measure the increase in skill level. In addition, the pre-training scores of participants at the very minimum patternmaking experience level were lower than those of participants with higher experience levels. Therefore, our instrument could be used in patternmaking courses in fashion design education to measure student skill development.